Thermal-electronic logic circuits: Scaling down. Issue 12 (December 2015) - Mizsei, János; Bein, Márton C.; Lappalainen, Jyrki; Juhász, László
Abstract: The thermal-electronic logic circuit (TELC) concept is a possible way to overcome the scaling down problems of the conventional CMOS integrated circuits, which have a very complex structure nowadays. The basic component of the TELC is the semiconductor–metal transition (SMT) switch, which is an extremely simple bulk type device. This work evaluates the effect of the scaling down on characteristics of the VO2 thermal-electronic switch. Different types (lateral and vertical) of VO2 resistors have been produced using focused ion beams and pulsed laser deposition. The measured switching time strongly correlates with the characteristic size of the device. The energy consumption (power-delay product) of the scaled-down switching device is estimated as a sum of the energy needed for heating the thermal diffusion length sized environment of the device, heating the device itself and the latent heat of phase transition of VO2 .